Novel interfaces for modeling and painting - Sun, Qian (2014)
The last decade witnessed the rapid development of interaction techniques. There has been a growing number of interactive devices, such as multi-touch displays, motion sensing input devices and voice input devices. Among them, touch based hardware are becoming more and more powerful in terms of screen size, resolution, accuracy, as well as the number of touch points, while the prices are dropping quickly. More and more electronic devices have emerged with touch screens, including smart phones, tablet PCs, GPS devices, ATM machines, various information and ticketing systems, etc. Compared to traditional WIMP interfaces that require the user to input information indirectly with IO devices, such as mice, touch-based interfaces, including multi-touch and sketch-based interfaces, allow the user to interact with the content directly using fingers and pens; a technique which has proved to be extremely intuitive and easy to learn. Additionally, multi-touch based interfaces can be more efficient than mouse-based interfaces and have great potential to facilitate collaboration among multiple people. Also, sketch-based interfaces can be very intuitive due to the simple sketch-based input and physical direct manipulation with the input screen. Because of the application-driven nature of computer graphics and the difficulty of visualizing and manipulating various aspects of computer graphics, including geometry creation, editing and so on, the interface and interaction method of applications play an important role in computer graphics applications. However, there are relatively few successful applications have been presented which have exploited novel interfaces in computer graphics applications due to the complexity of such applications. In this thesis, we demonstrate three graphics applications that use novel interfaces to improve the user interaction in terms of efficiency and intuitiveness. By conducting user studies for the specified applications and tasks, we also explore some touch interaction principles that might be followed up by later work. Our applications cover a wide range, including touch-based 2D drawing, surfaces texturing and 3D modeling of tall buildings.